As mudanças nas leis florestais e a quantificação de serviços ecossistêmicos em microbacias rurais - Rosário, Victor Alexandre Carlotti (Universidade Federal de São Carlos, 2018)
The demand for information about resources quantity and quality of a watershed, and how these resources are related with riparian forests, restoration, farming and Ecosystem Services (ES) production, are very debated nowadays. Thus, the determination of factors that directly and indirectly affect the quality and quantity of these resources, and how it affects the landscape dynamic, must be studied for a better balance between agriculture and environment. The objective of this study is quantify the potential of ES production related to soil conservation and carbon stock in different forest restoration scenarios and the adoptions of soil conservation practices in agriculture areas. Two micro watersheds were studied: Posses (Extrema – MG) and Ribeirão Vermelho (São Pedro – SP). Three scenarios were considered: the current land use and soil cover, the old Forest Code (1965 – scenario I), and the Native Vegetation Protection Law (NVPL, 2012 – scenario II). The metrics used in this evaluation were soil loss, soil retention and sedimentation. Carbon stock was estimated for current forest cover, for restoration areas and for the others current land covers and uses. To evaluate the soil conservation and agricultural practices were simulated different scenarios with and without conservation practices and different riparian forest protection buffers. Regarding the current scenario, the NVPL will increase the forest cover, decrease sedimentation, soil loss and increase the carbon stock for the Posses and Ribeirão Vermelho micro watersheds. It was verified that the a bigger forest cover (scenario I), provides less soil loss and less sediment that reaches the waterways when compared to landscapes with lower amount of native vegetation (scenario II). Therefore, the NVPL will reduce the area to be restored, the potential of recovery of forest cover and the ES production related with soil conservation in the micro watersheds studied compared to what would be obtained with the old forest code. In addition, the conservation practices adoption, with and without, influenced soil loss and sedimentation more than the riparian vegetation buffers, evidencing the importance of the adoption of good agricultural practices within the concept of forest restoration and landscape.
Forest laws changes and ecosystem services quantification in rural micro watershed
Keywords: Modelagem da paisagem; Equação Universal de Perda de Solo Revisada - RUSLE; Manejo do solo; Restauração florestal; Landscape modeling; Revised Universal Soil Loss Equation - RUSLE; Soil management; Forest restoration; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::HIDROLOGIA FLORESTAL; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::MANEJO FLORESTAL::ADMINISTRACAO FLORESTAL; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::MANEJO FLORESTAL::POLITICA E LEGISLACAO FLORESTAL; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::MANEJO FLORESTAL